Culture Wars and Enduring American Dilemmas - Thomson, Irene Taviss (Contemporary Political and Social Issues, 2010)
"The idea of a culture war, or wars, has existed in America since the 1960s-an underlying ideological schism in our country that is responsible for the polarizing debates on everything from the separation of church and state, to abortion, to gay marriage, to affirmative action. Irene Taviss Thomson explores this notion by analyzing hundreds of articles addressing hot-button issues over two decades from four magazines: National Review, Time, The New Republic, and The Nation, as well as a wide array of other writings and statements from a substantial number of public intellectuals. What Thomson finds might surprise you: based on her research, there is no single cultural divide or cultural source that can account for the positions that have been adopted. While issues such as religion, homosexuality, sexual conduct, and abortion have figured prominently in public discussion, in fact there is no single thread that unifies responses to each of these cultural dilemmas for any of the writers."